2022
DOI: 10.3389/fnagi.2022.890512
|View full text |Cite
|
Sign up to set email alerts
|

Application of Neurotoxin-Induced Animal Models in the Study of Parkinson’s Disease-Related Depression: Profile and Proposal

Abstract: Depression can be a non-motor symptom, a risk factor, and even a co-morbidity of Parkinson’s disease (PD). In either case, depression seriously affects the quality of life of PD patients. Unfortunately, at present, a large number of clinical and basic studies focused on the pathophysiological mechanism of PD and the prevention and treatment of motor symptoms. Although there has been increasing attention to PD-related depression, it is difficult to achieve early detection and early intervention, because the cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 126 publications
0
6
0
Order By: Relevance
“…Anxiety and depression are the most common neuropsychiatric disorders in patients who have also been diagnosed with PD, with between 40 and 50% being diagnosed with comorbid depression [ 7 ]. 6-OHDA and other neurotoxic models of PD are associated with anxiogenic- and depressive-like behaviors in mouse models [ 38 ]. CB2 activation with GW842166x treatment protected against 6-OHDA-induced decreases in dopamine release both in vitro ( Figure 3 ) and in vivo ( Figure 4 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Anxiety and depression are the most common neuropsychiatric disorders in patients who have also been diagnosed with PD, with between 40 and 50% being diagnosed with comorbid depression [ 7 ]. 6-OHDA and other neurotoxic models of PD are associated with anxiogenic- and depressive-like behaviors in mouse models [ 38 ]. CB2 activation with GW842166x treatment protected against 6-OHDA-induced decreases in dopamine release both in vitro ( Figure 3 ) and in vivo ( Figure 4 ).…”
Section: Resultsmentioning
confidence: 99%
“…The present study determines whether GW842166x exerts neuroprotective effects against 6-OHDA-induced loss of dopaminergic axonal terminals and dopamine release in vitro and in vivo. Neurotoxin-induced rodent models of PD exhibit depressive-like behaviors [ 38 ]. We also examined whether 6-OHDA-induced lesions of dopamine neurons causes anxiogenic- and depressive-like behavioral phenotypes and whether the CB2 agonist produces anxiolytic and anti-depressive-like effects.…”
Section: Introductionmentioning
confidence: 99%
“…A potential avenue for further research could be in animal models of PD neurodegeneration, specifically in the context of PD depression. A number of rodent studies utilizing neurotoxic compounds such as 1-Methyl-4-Phenyl-1,2,3,6-Tetrahydropyridine (MPTP), which cause selective dopaminergic neuron degeneration, report depression-like behaviours, even manifesting before the onset of motor impairments 41 . Importantly the onset of this depression-like phenotype is variable 42 , 43 , potentially allowing for a controlled model for assessment of specific cell type contributions to the variable onset of PD depression, as mediated by midbrain dopaminergic degeneration.…”
Section: Discussionmentioning
confidence: 99%
“…PD is a common and heterogeneous neurodegenerative disease characterized as a Lewy type α-synucleinopathy that is never restricted to the nigrostriatal system, and has both motor and non-motor manifestations including depression, anxiety and other neuropsychiatric signs and symptoms arising from a diverse neuroanatomical distribution of αSyn aggregates that causes a multitude of degenerative lesions involving a wide variety of nervous systems and networks. Among the non-motor manifestations of PD, depression is particularly important due to its negative impact on the course of the disease, its frequent combination with cognitive impairment and functional disability and impact on the quality of life of the patients and caregivers (Mou et al 2022 ). The morphological and molecular biochemical basis of depressive symptoms in PD is heterogeneous, and modern neuroimaging, neurochemical and neuropathological studies have provided insight into important pathobiological mechanisms, suggesting that DPD is associated with complex dysfunctions of multiple neurotransmitter nuclei and pathways, in particular widespread degeneration of both the dopaminergic and serotonergic systems, as well as early noradrenergic deficiency due to early degeneration of the LC.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of depression in de novo PD often reflects poor motor compensation (Lee et al 2018 ), and its severity was greater in non-tremor-dominant de novo patients (Weintraub et al 2015 ). Studies demonstrated that neurotoxin-induced PD models may exhibit depression-like behaviors, which sometimes manifest earlier than motor impairments (Mou et al 2022 ). However, due to an overlap with other symptoms primarily related to PD or side effects of medication, depression frequently remains unrecognized and undertreated (Laux 2022 ; Macías-García et al 2022 ; Orayj et al 2021 ; Politis et al 2010b ; Weintraub et al 2004 ).…”
Section: Introductionmentioning
confidence: 99%